The way to the waterfront. A walking methodology for the analysis of public space - Ochoa, R. (Ángulo Recto, 2017)
In an approach to the city that refuses to be confined to its merely physical features and includes an interdisciplinary perspective, it is crucial to find mechanisms to study its multiple dimensions and experiences. This paper proposes a reflection on the existing research in fields such as Architecture and Urbanism, discussing the importance of specific methodologies for the analysis of territory. This discussion builds on an example of research about the connections between a city and its waterfront, the case of Lisbon. Here, the main methodology is based on in situ observation and its subsequent systematization, finally configuring a graphic and visual approach to the study of public space. This methodology can be applied to other urban realities not only for the analysis of public space but also for its design.